Using Implementation Science-Informed Strategies to Improve Transitions of Care for Patients with Venous Thromboembolism. - Ciemins, Elizabeth L.; Grant, Cori C.; Tallam, Meghana; Rattelman, Cori; Lindberg, Curt; Williams, Rae Ann; Christensen, Paige S.; Thygeson, N. Marcus (Joint Commission Journal on Quality & Patient Safety, 2025)
Venous thromboembolism (VTE), including deep vein thrombosis and pulmonary embolism, are common causes of preventable hospital death. Most VTEs diagnosed in the outpatient setting are directly linked to a recent hospitalization or surgery. A type 2 effectiveness-implementation hybrid study was conducted to develop and implement targeted interventions to improve care for patients with VTE in six US health systems. Primary outcomes included (1) 7-day follow-up after VTE diagnosis (phone calls, office visits); (2) VTE–related hospitalizations or emergency department (ED) visits within 45 days of acute VTE diagnosis; and (3) anticoagulant-associated adverse drug events (ADEs). Qualitative comparative analysis (QCA) identified interventions associated with improved care for patients with VTE. Among 1,265 patients, follow-up within 7 days of an index VTE diagnosis improved from 25.2% to 33.6% (p < 0.0001); among 2,002 patients, hospitalizations/ED visits within 45 days of VTE diagnosis decreased across settings from 7.8% to 6.3% (p = 0.033), and the rate of anticoagulant-associated ADEs remained low (3.1% to 3.4%, p = 0.528). Factors characteristic of improving 7-day follow-up included combinations of (1) safer prescribing and management of anticoagulants and standardized protocols with centralized care processes or (2) safer prescribing and management of anticoagulants with improved care team communication and expanded anticoagulation clinic access for patients prescribed direct oral anticoagulants. Factors associated with 45-day hospitalization/ED visits improvement included high baseline rates of 7-day follow-up, high rates of baseline 45-day hospitalization/ED visits (larger opportunity), improved care team communication, and improved standardization and centralization of protocols. Combinations of interventions, tailored to local context and team dynamics, improved ambulatory follow-up rates and reduced VTE–related utilization. Health systems may benefit from considering novel, implementation science–informed strategies to foster improvement.